The determinants of banks' capital structure in SAARC economies - Raja, Rehan; Adam Sa'ad, Auwal; Fu, Guo Hong; Khan, Muhammad Asghar (Learning Gate, 2024)
The capital structure determinants for South Asian banks are required to be exposed. This investigation attempts to address the existing gap by examining the capital structure determinants for the South Asian Association for Regional Cooperation (SAARC) countries. To accomplish the main objective, the Panel Data of 52 banks is collected from the four main regional economies for the period starting from 2012 to 2022. The methodology is based on the estimation of constructed models by executing Static Panel Data analysis and Dynamic Panel Data analysis via the Generalized Method of Moments (GMM). The investigation discovered that tangibility, growth, profitability and non- performing loans have positive significant influences, whereas, liquidity and gross domestic products have negative significant impacts on the regional banks' capital structure. Also, the significant lagged variable and the presence of adjustment speed suggest the implementation of the Dynamic Trade-Off theory in the SAARC countries' banking sectors. The findings will help regulatory bodies develop a harmonization policy to enhance financial integration among SAARC economies via adopting identified capital structure determinants.